Adaptation, implementation, and evaluation of an online health sciences training program for brief smoking intervention: A pre-post study in four European countries. - Pardavila-Belio, Miren Idoia; Moreno-Arroyo, Carmen; Romero-Clará, Olga; Tricas-Sauras, Sandra; Barroso, Tereza; Duaso, María; Vilaplana, Jordi; Agüera, Zaida; Canga-Armayor, Navidad; Demedts, Dennis; Elliott, Rebecca; Godin, Isabelle; et al. (Nurse Education Today, 2023)
Tobacco cessation intervention has a positive impact on quality of care. For health professionals, limited competency in this area may be associated with poor training during their academic programs. There is a clear need to further develop and implement training programs to improve tobacco cessation knowledge, skills, and attitudes among healthcare students. The aim of this study was to assess the effectiveness of the innovative online training program "Brief Intervention in Smoking Cessation" for healthcare students to improve their knowledge, skills, and attitudes. A pre-post evaluation study with a satisfaction assessment tool was used. Seven universities from four European countries, including Belgium, Portugal, Spain, and the United Kingdom, participated. One thousand and seventy-two (1072) undergraduate students participated, with 851 completing the online program. All participants completed the " Brief Intervention in Smoking Cessation " online program, which consisted of five theoretical modules, five videos, and three virtual simulation cases between January 2020 and June 2022. Knowledge was assessed by a multiple-choice test, and practical skills were assessed by a simulation algorithm, both of which were developed by education and smoking cessation experts. Competency was achieved when students successfully completed both assessments. Satisfaction was measured using an ad hoc 16-item questionnaire. Pre-post changes in knowledge were assessed using a paired Student's t -test. Eighty-six percent of the students achieved smoking cessation competency. Students significantly improved their knowledge score on a scale of 0 to 10 points, with a mean pre-program score of 3.79 vs a mean post-program score of 7.33 ([−3.7 - -3.4] p < 0.001), acquiring sufficient attitudes and skills (simulation mean of 7.4 out of 10 points). Students were highly satisfied with the program (8.2 out of 10) and recommended it to other students (8.4 out of 10). The "Brief Intervention in Smoking Cessation" online training program is effective for the acquisition of smoking cessation competencies among European health profession students.